Pain management in postoperative bone fracture patients: A systematic scoping review - Nurjanah, Siti; Mulyana, Aep Maulid; Arhustia, Hesti Dina; Ayuningsih, Risna; Fazriyyah, Yuni Fuji; Rahayu, Urip; Pebrianti, Sandra; Arifin, Hidayat (Palembang MediRose Publisher, 2023)
Background: A fracture is a condition in which the continuity of bone tissue is broken, causing stress and pain during the healing process. Therefore, the management of pain in postoperative bone fracture patients should be addressed.. Objective: The aim is to identify interventions for managing pain in patients with postoperative bone fractures. Design: A systematic scoping review. Data Sources: The search process was conducted from March 8 to March 15, 2022, using the following databases: PubMed, CINAHL, and Science Direct. Review Methods: PRISMA flowcharts were used for the systematic review. Articles published in the last five years (2018-2022) were included, focusing on full-text articles, randomized controlled trials (RCTs), and cohort studies that discussed the topic of postoperative pain management in fracture patients. The search yielded a total of 4,324 articles from the four databases. After screening by year, 819 articles were obtained. Based on the full text and abstracts of 432 articles, and applying exclusion and inclusion criteria, five articles were selected. Results: The five articles demonstrated that pain management in postoperative bone fracture patients can be achieved through various pharmacological approaches, including peripheral nerve block anesthesia, antioxidants (vitamin C), intravenous tranexamic acid, intravenous dexamethasone, and the use of calculators and comprehensive pain plans as management tools. Conclusions: This study recommends that healthcare professionals apply and further develop the findings as a pain management strategy for postoperative bone fracture patients.